DESAIN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA BUDIDAYA IKAN MUJAIR (STUDI KASUS PADA UD BLESS) - Nender, Christina; Korompis, Sintia Nurani; Pantow, Andreuw Kristian; Toweula, Alpindos; Tangon, Joseph Nugraha (Journal of Information System, Applied, Management, Accounting and Research, 2024)
UD Bless is an entity that runs a mujair fish farming business. The fish farming process starts from nursery or spawning, hatchery, enlargement until the fish is ready to be harvested/sold. This business is located in Eris Village, Eris District. In running its business, UD. Bless has not carried out financial management in accordance with applicable standards due to limited knowledge or understanding of proper financial management. The purpose of this research is to compile UD's financial statements. Bless in accordance with SAK EMKM. This research was conducted at UD. Bless. Research data obtained from primary and secondary sources. The analysis tool used is descriptive analysis. The findings obtained after conducting research are UD. Bless has not prepared financial reports and still conducts simple financial records. The financial statements made by researchers for UD. Bless in accordance with SAK EMKM which consists of Income Statement, Statement of Financial Position, and Notes to Financial Statements. Researchers recommend to UD. Bless in order to use the financial statements that have been made as guidelines for the preparation of financial statements in the following periods.